2016
DOI: 10.1021/acs.jpcc.6b04429
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Behavior of Glucosamine-Based, Pyrimidine-Fused Heterocycles as Green Corrosion Inhibitors for Mild Steel: Experimental and Theoretical Studies

Abstract: Effects of electron donating (−CH 3 and −OH) and electron withdrawing (−NO 2 ) substituents on the corrosion inhibition efficiency of four glucosamine-based, substituted, pyrimidine-fused heterocycles (CARBs) on mild steel corrosion in 1 M HCl have been investigated using gravimetric, electrochemical, surface morphology (SEM, AFM, and EDX), and computational techniques. Gravimetric studies showed that protection performances of the compounds increase with increase in concentration. Both electron withdrawing (−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
168
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 444 publications
(174 citation statements)
references
References 83 publications
4
168
0
2
Order By: Relevance
“…In continuation of our works on corrosion inhibition property of carbohydrate based corrosion inhibitors8, the present study considers the synthesis and investigation of corrosion inhibition effect of three novel D-glucose derivatives of dihydropyrido [2,3-d:6,5-d′] dipyrimidine-2, 4, 6, 8(1H,3H, 5H,7H)-tetraone namely, 5-((1S,2R,3R,4R)-1,2,3,4,5-pentahydroxypentyl)-10-phenyl-9,10-dihydropyrido[2,3-d:6,5-d′]dipyrimidine-2,4,6,8 (1H,3H, 5H,7H)- tetraone (GPH-1), 10- (4-hydroxy phenyl)- 5-((1S, 2R, 3R, 4R) -1,2,3,4,5-pentahydroxypentyl)-9,10-dihydropyrido [2,3-d:6,5-d′] dipyrimidine-2, 4, 6, 8(1H,3H, 5H,7H)-tetraone (GPH-2) and 10- (4-(methoxyphenyl)-5-((1S, 2R, 3R, 4R)-1, 2, 3, 4, 5-pentahydroxypentyl)-9,10-dihydropyrido[2,3-d:6,5-d′]dipyrimidine-2, 4, 6, 8(1H, 3H, 5H, 7H)-tetraone (GPH-3). The synthesized compounds were tested as prospective inhibitors of mild steel corrosion in hydrochloric acid using gravimetric, electrochemical impedance spectroscopy (EIS), potentiodynamic polarization, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), atomic force microscopy (AFM), quantum chemical calculations and Monte Carlo simulations techniques.…”
mentioning
confidence: 95%
“…In continuation of our works on corrosion inhibition property of carbohydrate based corrosion inhibitors8, the present study considers the synthesis and investigation of corrosion inhibition effect of three novel D-glucose derivatives of dihydropyrido [2,3-d:6,5-d′] dipyrimidine-2, 4, 6, 8(1H,3H, 5H,7H)-tetraone namely, 5-((1S,2R,3R,4R)-1,2,3,4,5-pentahydroxypentyl)-10-phenyl-9,10-dihydropyrido[2,3-d:6,5-d′]dipyrimidine-2,4,6,8 (1H,3H, 5H,7H)- tetraone (GPH-1), 10- (4-hydroxy phenyl)- 5-((1S, 2R, 3R, 4R) -1,2,3,4,5-pentahydroxypentyl)-9,10-dihydropyrido [2,3-d:6,5-d′] dipyrimidine-2, 4, 6, 8(1H,3H, 5H,7H)-tetraone (GPH-2) and 10- (4-(methoxyphenyl)-5-((1S, 2R, 3R, 4R)-1, 2, 3, 4, 5-pentahydroxypentyl)-9,10-dihydropyrido[2,3-d:6,5-d′]dipyrimidine-2, 4, 6, 8(1H, 3H, 5H, 7H)-tetraone (GPH-3). The synthesized compounds were tested as prospective inhibitors of mild steel corrosion in hydrochloric acid using gravimetric, electrochemical impedance spectroscopy (EIS), potentiodynamic polarization, scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDX), atomic force microscopy (AFM), quantum chemical calculations and Monte Carlo simulations techniques.…”
mentioning
confidence: 95%
“…This is achieved by density functional theory (DFT). DFT is one of the most important methods used in theoretical chemistry for corrosion inhibition to accurately predict the inhibition efficiencies based on the calculations provided by mechanistic information about metal-inhibitor interactions and can be performed for inhibitor molecules even before their synthesis [100][101][102][103][104][105].…”
Section: Green Corrosion Inhibitor Based On Ionic Liquidsmentioning
confidence: 99%
“…Polarization results indicated that majority of these compounds behave as mixed type inhibitors. However, there are some compounds which act as cathodic-type inhibitors [16,28] and anodic inhibitors [21]. The adsorption of many of these compounds on steel surface followed Langmuir adsorption isotherm, where as few of the compounds were found to obey the Dubinin-Radushkevich adsorption isotherm [33,34], Frumkin adsorption isotherm [7] and Temkin's adsorption isotherm [21].…”
Section: Corrosion Inhibitorsmentioning
confidence: 99%